Agent to the stars - Scalzi, John 1969- (Tor, 2005)
The space-faring Yherajk have come to begin humanity's first interstellar friendship. Unfortunately, they are hideous and they smell like rotting fish. They're going to need the best agent in Hollywood to make the friendly, odiferous creatures palatable to humanity.